Alpha-alumina carrier and preparation method thereof, silver catalyst for ethylene epoxidation and ethylene oxidation method

By using different forms of non-spherical organic polymer particles as pore-forming agents, the pore structure of the alumina support is improved, and the problem of insufficient activity, selectivity and stability of silver catalysts is solved, and an efficient ethylene oxidation reaction is achieved.

CN119524826AActive Publication Date: 2025-02-28CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202311085415.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-28
Estimated Expiration
2043-08-25

AI Technical Summary

Technical Problem

In the prior art, the activity, selectivity and stability of the silver catalyst are insufficient, and the pore structure of the alumina support is uneven, which affects the performance of the catalyst.

Method used

Different forms of non-spherical organic polymer particles are used as pore-forming agents to improve the pore connectivity between the carrier through specific pore forms and structures, and improve permeability, thereby preparing a highly active and selective silver catalyst.

Benefits of technology

Through the improved support preparation method, the activity and selectivity of the silver catalyst are significantly improved, the gas diffusion distance is shortened, and the stability of the catalyst is also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004416507800000091
    Figure BDA0004416507800000091
  • Figure BDA0004416507800000092
    Figure BDA0004416507800000092
  • Figure BDA0004416507800000171
    Figure BDA0004416507800000171
Patent Text Reader

Abstract

The invention belongs to the field of catalysts, and relates to an alpha-alumina carrier and a preparation method thereof, a silver catalyst for ethylene epoxidation and an ethylene oxidation method. The preparation method of the alpha-alumina carrier comprises the following steps: preparing a solid mixture containing the following components: alpha-Al2O3 trihydrate, pseudo Al2O3 monohydrate, a pore forming agent, a combustible lubricating material, a fluoride mineralizer and an alkaline earth metal compound; wherein the pore forming agent is non-spherical organic polymer particles; the solid mixture, a binder and optional water are mixed, kneaded and subjected to extrusion molding, and a molded body is obtained; and drying and roasting the molded body to obtain the alpha-alumina carrier. According to the invention, non-spherical organic polymer particles with different forms are used as the pore-forming agent, the pore-forming agent has no residue in the roasting process of the carrier, a specific pore form can be formed, the connectivity between carrier pores is improved, the tortuosity is reduced, the permeability is improved, and the activity and selectivity of the catalyst can be obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of catalysts, and more specifically, relates to a method for preparing an alpha-alumina carrier, an alpha-alumina carrier prepared by the preparation method, a silver catalyst prepared by the alpha-alumina carrier, and an ethylene oxidation method. Background Art

[0002] Under the action of silver catalyst, ethylene oxidation mainly produces ethylene oxide, while side reactions produce carbon dioxide and water. Activity, selectivity and stability are the main performance indicators of silver catalysts. Among them, activity generally refers to the reaction temperature required for the ethylene oxide production process to reach a certain reaction load. The lower the reaction temperature, the higher the activity of the catalyst; selectivity refers to the ratio of the number of moles of ethylene converted into ethylene oxide to the total number of moles of ethylene in the reaction; and stability is expressed as the rate of decrease of activity and selectivity. The smaller the rate of decrease, the better the stability of the catalyst. At present, silver catalysts can be mainly divided into three types, namely high-activity, high-selectivity and medium-selectivity silver catalysts. Due to the increasing scarcity of petroleum resources and the requirement of energy conservation, high-selectivity and medium-selectivity silver catalysts have been widely used in industrial production in recent years and replaced the original high-activity silver catalysts.

[0003] The performance of silver catalysts is not only closely related to the composition and preparation method of the catalyst, but also closely related to the performance and preparation method of the carrier used in the catalyst. At present, silver catalysts generally use α-alumina as a carrier. The pores of alumina carriers can be divided into three types: the first type is the pores between primary particle crystals, which are mainly the dehydration pores of the alumina raw material crystals, which are basically 1-2nm in size. The gaps between parallel plate surfaces; the second type is the pores between secondary particles of alumina raw materials, which change with the escape of water and the change of crystal phase during roasting, and are pores larger than tens of nanometers; the third type is the defective pores and macropores generated during the molding of pore-forming agents and carriers. The pore structure of the carrier will affect the physical properties, and thus affect the performance of the catalyst.

[0004] In the prior art, the pore-forming agents used to prepare alumina carriers mainly include starch, petroleum coke, carbon powder, sesbania powder, coconut shell charcoal, sawdust, etc. These pore-forming agents are usually affected by the place of origin, and the quality is unstable. Different batches introduce different impurities into the carrier, and most of them are obtained by crushing to obtain the appropriate particle size. The particle size distribution range is relatively wide, which is not conducive to achieving uniform and controllable pore structure of the carrier, and is also not conducive to the performance of the silver catalyst. When spherical or quasi-spherical organic polymer particles with uniform and controllable particle size are used as pore-forming agents, there is no residue during the carrier roasting process, and the pore structure parameters of the carrier can be adjusted within a certain range, so that the carrier pore size is unimodal or multimodal distribution, and the pore size distribution of a single peak is relatively narrow, but the connectivity between different pores still has a lot of room for improvement. Summary of the invention

[0005] In view of the above-mentioned prior art, the inventors of the present invention have conducted extensive and in-depth research in the field of silver catalysts and carrier preparation thereof, and found that when non-spherical organic polymer particles of different forms are used as pore formers, there is no residue during the carrier calcination process, and a specific pore morphology can be formed, the connectivity between the pores is improved, the tortuosity is reduced, and the permeability is improved. When the silver catalyst prepared from the carrier is used for ethylene oxidation to produce ethylene oxide, the gas diffusion distance can be effectively shortened, and the catalyst activity and selectivity are significantly improved. Based on the above-mentioned findings, the purpose of the present invention is to provide an α-alumina carrier and a preparation method thereof, a silver catalyst for ethylene epoxidation, and an ethylene oxidation method.

[0006] In order to achieve the purpose of the present invention, the first aspect of the present invention provides a method for preparing an α-alumina carrier, comprising the following steps:

[0007] S1. Prepare a solid mixture having the following components: α-A12O3 trihydrate, pseudo-monohydrate A12O3, a pore-forming agent, a burnable lubricating material, a fluoride mineralizer, and an alkaline earth metal compound; wherein the pore-forming agent is a non-spherical organic polymer particle;

[0008] S2. The solid mixture in step S1, the binder and optionally water are mixed, kneaded and extruded to obtain a molded body;

[0009] S3. Drying and calcining the molded body in step S2 to obtain the α-alumina carrier.

[0010] The second aspect of the present invention provides an α-alumina carrier prepared by the preparation method.

[0011] The third aspect of the present invention provides a silver catalyst for ethylene epoxidation, the silver catalyst comprising the following components:

[0012] a) the α-alumina carrier;

[0013] b) an active component silver deposited on component a);

[0014] c) alkali metals and / or alkaline earth metals, or compounds based on alkali metals and / or alkaline earth metals;

[0015] d) rhenium metal and / or rhenium-based compounds; and

[0016] e) Optionally, a rhenium co-promoter selected from at least one metal selected from chromium, molybdenum, tungsten and manganese, and / or selected from compounds based on at least one metal selected from chromium, molybdenum, tungsten and manganese.

[0017] The fourth aspect of the present invention provides an ethylene oxidation method, which comprises: subjecting ethylene to an ethylene epoxidation reaction under the action of the α-alumina carrier and / or the silver catalyst to obtain ethylene oxide.

[0018] The present invention uses non-spherical organic polymer particles of different forms as pore-forming agents, which leave no residue during the carrier calcination process and can form specific pore morphology, thereby improving the connectivity between the carrier pores, reducing tortuosity and improving permeability. Compared with the prior art, the silver catalyst prepared by the α-alumina carrier provided by the present invention can effectively shorten the gas diffusion distance and significantly improve the catalyst activity and selectivity when used for ethylene oxidation to produce ethylene oxide.

[0019] Other features and advantages of the present invention will be described in detail in the following detailed description. DETAILED DESCRIPTION

[0020] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0021] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0022] In order to achieve the purpose of the present invention, the first aspect of the present invention provides a method for preparing an α-alumina carrier, comprising the following steps:

[0023] S1. Prepare a solid mixture having the following components: α-A12O3 trihydrate, pseudo-monohydrate A12O3, a pore-forming agent, a burnable lubricating material, a fluoride mineralizer, and an alkaline earth metal compound; wherein the pore-forming agent is a non-spherical organic polymer particle;

[0024] S2. The solid mixture in step S1, the binder and optionally water are mixed, kneaded and extruded to obtain a molded body;

[0025] S3. Drying and calcining the molded body in step S2 to obtain the α-alumina carrier.

[0026] The inventors of the present invention have found that the use of non-spherical organic polymer particles of different forms as pore-forming agents leaves no residue during the carrier calcination process and can form specific pore morphology, thereby improving the connectivity between carrier pores, reducing tortuosity and improving permeability.

[0027] In the present invention, "optional water" means that water may or may not be added, and the water here refers to additionally added water, and does not include water inherently contained in other components.

[0028] According to the present invention, in step S3, the drying and calcining methods can be carried out with reference to the conventional methods in the art. Preferably, the molded body can be dried to contain less than 10% by weight of free water, the drying temperature can be 80 to 120°C, and the drying time is controlled at 1 to 24 hours according to the moisture content. The calcination converts all the aluminum oxide into α-A12O3, and the calcination time can be 1 to 20 hours, preferably 2 to 15 hours; the maximum calcination temperature can be 1200 to 1500°C. The calcination converts all the aluminum oxide into α-A12O3.

[0029] According to the present invention, preferably, the non-spherical organic polymer particles are irregular particles of various forms, and more preferably, the non-spherical organic polymer particles are at least one of rod-shaped particles, peanut-shaped particles, dumbbell-shaped particles, snowman-shaped particles, mushroom cap-shaped particles, multi-headed particles, disc-shaped particles, particles with concave and convex edges, and particles with protruding rods.

[0030] According to the present invention, preferably, the equivalent diameter of the non-spherical organic polymer particles is 0.5 to 50 μm, preferably 2 to 30 μm.

[0031] According to the present invention, preferably, the organic polymer forming the non-spherical organic polymer particles is selected from at least one of polystyrene (PS), polymethyl methacrylate (PMMA), polyvinyl alcohol (PVA), butyl acrylate-methyl methacrylate copolymer and styrene-methyl methacrylate copolymer.

[0032] According to the present invention, preferably, the non-spherical organic polymer particles are added in an amount of 0.1 to 20 wt %, preferably 1.0 to 15 wt %, based on the total weight of the solid mixture.

[0033] According to the present invention, preferably, the particle size of the trihydrate α-A12O3 is 25-300 μm; the addition amount of the trihydrate α-A12O3 is 10-85wt%, preferably 20-82wt%, of the total weight of the solid mixture.

[0034] According to the present invention, preferably, the particle size of the pseudo-monohydrate A12O3 is less than 100 μm; the added amount of the pseudo-monohydrate A12O3 is 10 to 55 wt%, preferably 15 to 45 wt%, of the total weight of the solid mixture.

[0035] In the present invention, the pseudo-monohydrate A12O3 reacts with acid during the kneading process and is converted into a sol, which acts as a binder. It is also converted into stable α-A12O3 during the high-temperature calcination process and becomes a part of the α-A12O3 carrier.

[0036] According to the present invention, preferably, the burnable lubricating material is vaseline and / or white oil; the addition amount of the burnable lubricating material is 0.01-8.0wt%, preferably 0.1-5.0wt%, of the total weight of the solid mixture.

[0037] According to the present invention, the addition of the burnable lubricating material is to make the kneaded material easy to shape and granulate. At the same time, an oxidation reaction occurs during the roasting process of the material, and the generated gas escapes. When the carrier is made, no impurities are introduced or as little as possible is introduced, thereby not affecting the performance of the catalyst.

[0038] According to the present invention, preferably, the fluoride mineralizer is at least one of hydrogen fluoride, aluminum fluoride, ammonium fluoride, magnesium fluoride and cryolite; the amount of the fluoride mineralizer added is 0.05-8.0wt% of the total weight of the solid mixture, preferably 0.5-5.0wt%.

[0039] According to the present invention, preferably, the alkaline earth metal compound is at least one of oxides, nitrates, acetates, oxalates and sulfates of strontium and / or barium; the amount of the alkaline earth metal compound added is 0.01 to 5.0 wt %, preferably 0.05 to 2.0 wt % of the total weight of the solid mixture.

[0040] According to the present invention, preferably, the binder is an acid, and the acid is provided in the form of an aqueous solution of the acid, preferably an aqueous nitric acid solution, and the weight ratio of nitric acid to water in the aqueous nitric acid solution is 1: (1.25-10); the amount of the binder used is 25-60wt% of the total amount of the solid mixture.

[0041] According to the present invention, in step S2, the solid mixture obtained in step S1 and the binder are kneaded with optional water, and the binder and the pseudo-water Al2O3 in the mixture generate aluminum sol, and the components are bonded together to obtain a paste, and then the paste is extruded to obtain a molded body. The amount of the binder added can be the conventional amount in the art, and preferably, based on the total weight of the solid mixture, the amount of the binder added is 25-60wt% of the total weight of the solid mixture. In the present invention, the type of the binder is well known to those skilled in the art, for example, including acid, the acid is usually provided in the form of an aqueous solution of the acid, preferably an aqueous nitric acid solution, and the weight ratio of nitric acid to water in the aqueous nitric acid solution is preferably 1: (1.25-10).

[0042] According to the present invention, preferably, the binder and pseudo-monohydrate Al2O3 are provided in whole or in part in the form of aluminum sol.

[0043] The second aspect of the present invention provides an α-alumina carrier prepared by the preparation method.

[0044] According to the present invention, preferably, the α-alumina carrier has the following characteristics: α-A12O3 content is more than 90%; crushing strength is 30 to 280N / grain, preferably 80 to 180N / grain; specific surface area is 0.3 to 2.5m 2 / g, preferably 1.0 to 2.2 m 2 / g; water absorption rate is 30-75%, preferably 50-70%; pore volume is 0.30-0.90ml / g, preferably 0.45-0.70ml / g; tortuosity is 4-10, preferably 4-7; permeability is 30-200mdarcy, preferably 50-200mdarcy.

[0045] In the present invention, the crushing strength of the carrier is measured by a DLⅡ intelligent particle strength tester, and a carrier sample is selected, and the radial crushing strength is measured and the average value is taken; the water absorption rate is measured by a boiling method; the specific surface area is measured by a nitrogen physical adsorption BET method; the pore volume, tortuosity and permeability are measured by a mercury injection method.

[0046] The third aspect of the present invention provides a silver catalyst for ethylene epoxidation, the silver catalyst comprising the following components:

[0047] a) the α-alumina carrier;

[0048] b) an active component silver deposited on component a);

[0049] c) alkali metals and / or alkaline earth metals, or compounds based on alkali metals and / or alkaline earth metals;

[0050] d) rhenium metal and / or rhenium-based compounds; and

[0051] e) Optionally, a rhenium co-promoter selected from at least one metal selected from chromium, molybdenum, tungsten and manganese, and / or selected from compounds based on at least one metal selected from chromium, molybdenum, tungsten and manganese.

[0052] According to the present invention, in the above-mentioned silver catalyst, based on the total weight of the silver catalyst, the mass content of silver is 5-37%, preferably 8-32%; the mass content of alkali metal is 5-3000ppm, preferably 10-2000ppm; the mass content of alkaline earth metal is 50-20000ppm, preferably 100-15000ppm; the mass content of rhenium metal is 10-2000ppm, preferably 100-1500ppm; the content of co-auxiliary agent is 0-1500ppm, preferably 0-1000ppm, calculated as the metal in the co-auxiliary agent.

[0053] The silver catalyst of the present invention can be prepared in a conventional manner by impregnating the above-mentioned α-alumina carrier with a solution containing a silver compound, an organic amine, an alkali metal promoter, an alkaline earth metal promoter, a rhenium promoter and optional co-promoters.

[0054] The organic amine may be any organic amine compound suitable for preparing a silver catalyst for producing ethylene oxide, as long as the organic amine compound can form a silver amine complex with a silver compound. For example, the organic amine may be selected from one or more of pyridine, butylamine, ethylenediamine, 1,3-propylenediamine and ethanolamine, preferably a mixture of ethylenediamine and ethanolamine.

[0055] The alkali metal additive may be a compound of lithium, sodium, potassium, rubidium or cesium or a combination of any two thereof, such as their nitrates, sulfates or hydroxides, or a combination of any two or more of the aforementioned compounds, preferably cesium sulfate and / or cesium nitrate.

[0056] The alkaline earth metal additive can be a compound of magnesium, calcium, strontium or barium, such as their oxides, oxalates, sulfates, acetates or nitrates, or a combination of any two or more of the foregoing compounds, preferably a compound of barium or strontium, more preferably barium acetate and / or strontium acetate. The alkaline earth metal additive can be applied to the support before, simultaneously with or after the silver is impregnated, or can be impregnated on the support after the silver compound is reduced.

[0057] The rhenium-containing auxiliary agent may be rhenium oxide, perrhenic acid, perrhenate, or a mixture thereof, preferably perrhenic acid and / or perrhenate, such as perrhenic acid, cesium perrhenate, and ammonium perrhenate.

[0058] The co-promoter containing the rhenium promoter can be a compound of any transition metal in the periodic table, or a mixture of several transition metal compounds, preferably one or more metals of chromium, molybdenum, tungsten and manganese, and / or compounds based on one or more elements of chromium, molybdenum, tungsten and manganese, such as one or more of chromic acid, chromium nitrate, tungstic acid, cesium tungstate, molybdic acid, ammonium molybdate, manganese acid and potassium permanganate. The rhenium promoter and its co-promoter can be applied to the support before, at the same time or after the silver is impregnated, or can be impregnated on the support after the silver compound is reduced. The activity, selectivity and stability of the activity and selectivity of the obtained silver catalyst can be further improved by adding the rhenium promoter and its co-promoter.

[0059] According to a specific embodiment of the present invention, the preparation method of the silver catalyst comprises the following steps:

[0060] (1) impregnating the porous α-alumina support with a solution containing a sufficient amount of a silver compound, an organic amine, an alkali metal promoter, an alkaline earth metal promoter, a rhenium promoter and a co-promoter;

[0061] (2) filtering off the impregnation liquid and drying the impregnated support; and

[0062] (3) activating the carrier obtained in step (2) in an oxygen-containing mixed gas to prepare the silver catalyst.

[0063] In the preparation of the silver catalyst of the present invention, silver nitrate is first mixed with an ammonium oxalate solution to generate silver oxalate, the silver oxalate is dissolved in an organic amine to form a silver amine solution, and then the above-mentioned additives are added to form an impregnation solution; then the prepared impregnation solution is used to impregnate the above-mentioned α-alumina carrier, drained, and maintained in an air flow or a nitrogen-oxygen mixed gas with an oxygen content of not more than 21% by weight (such as 8% by weight of oxygen) at a temperature range of 180-700° C., preferably 200-500° C. for 0.5-120 minutes, preferably 1-60 minutes for thermal decomposition to obtain a finished silver catalyst.

[0064] The fourth aspect of the present invention provides an ethylene oxidation method, which comprises: subjecting ethylene to an ethylene epoxidation reaction under the action of the α-alumina carrier and / or the silver catalyst to obtain ethylene oxide.

[0065] The present invention will be further described below in conjunction with embodiments, but the scope of the present invention is not limited to these embodiments.

[0066] In the following examples and comparative examples:

[0067] The initial performance and stability of various silver catalysts were tested using a laboratory reactor (hereinafter referred to as "microreactor") evaluation device. The reactor used in the microreactor evaluation device is a stainless steel tube with an inner diameter of 4 mm, and the reactor is placed in a heating jacket. The catalyst loading volume is 1 mL, and there is an inert filler at the bottom, so that the catalyst bed is located in the constant temperature zone of the heating jacket.

[0068] The activity and selectivity assay conditions used are shown in Table 1:

[0069] Table 1

[0070]

[0071] When the above reaction conditions are stably reached, the gas composition at the reactor inlet and outlet is continuously measured. The selectivity S is calculated according to the following formula after volume shrinkage correction is performed on the measured results:

[0072]

[0073] Among them, ΔEO is the difference in ethylene oxide concentration between the reactor outlet gas and the inlet gas, ΔCO2 is the difference in carbon dioxide concentration between the reactor outlet gas and the inlet gas, and the average of more than 10 groups of test data is taken as the test result of the day.

[0074] Lateral crushing strength of alumina carrier: A DLⅡ intelligent particle strength tester was used to select alumina carrier samples, and the radial crushing strength was measured and the average value was taken.

[0075] Water absorption: Determined by boiling method.

[0076] Specific surface area: measured by nitrogen physical adsorption BET method.

[0077] Pore ​​volume, tortuosity and permeability: measured by mercury injection method.

[0078] Examples 1-9 are used to illustrate the preparation of the alumina carrier provided by the present invention.

[0079] Example 1

[0080] 3000g of 25-300μm α-A12O3 trihydrate, 2400g of pseudo-monohydrate A12O3 less than 100μm, 300g of shaped polystyrene (PS) particles with protruding rods of equivalent diameter 18μm, 120g of aluminum fluoride and 40g of barium nitrate were put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) were added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The kneaded carrier was placed in a bell kiln, heated from room temperature to 1400°C over 33 hours, and calcined at 1400°C for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0081] Example 2

[0082] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 60g of shaped polystyrene (PS) particles with protruding rods of equivalent diameter 18μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying is carried out at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, and the temperature is raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0083] Example 3

[0084] 3000g of 25-300μm α-A12O3 trihydrate, 2400g of pseudo-monohydrate A12O3 less than 100μm, 900g of shaped polystyrene (PS) particles with protruding rods of equivalent diameter 18μm, 120g of aluminum fluoride and 40g of barium nitrate were put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) were added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The kneaded carrier was placed in a bell kiln, heated from room temperature to 1400°C over 33 hours, and calcined at 1400°C for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0085] Example 4

[0086] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of shaped polystyrene (PS) particles with protruding rods of equivalent diameter 2μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, and the temperature is raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0087] Example 5

[0088] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of shaped polystyrene (PS) particles with protruding rods of equivalent diameter 30μm, 120g of aluminum fluoride and 40g of barium nitrate were put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) were added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The kneaded carrier was placed in a bell kiln, heated from room temperature to 1400°C over 33 hours, and calcined at 1400°C for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0089] Example 6

[0090] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of rod-shaped polyvinyl alcohol (PVA) particles with an equivalent diameter of 10μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0091] Example 7

[0092] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of mushroom-shaped polystyrene (PS) particles with an equivalent diameter of 10μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0093] Example 8

[0094] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of snowman-shaped styrene-methyl methacrylate copolymer particles with an equivalent diameter of 10μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0095] Example 9

[0096] 3000g of α-A12O3 trihydrate with a diameter of 25 to 300μm, 2400g of pseudo-monohydrate A12O3 with a diameter less than 100μm, 200g of shaped polystyrene (PS) particles with protruding rods with an equivalent diameter of 18μm, 200g of rod-shaped polymethyl methacrylate (PMMA) particles with an equivalent diameter of 10μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying is carried out at 80 to 120℃ for more than 2 hours to reduce the free water content to less than 10%. The kneaded carrier was placed in a bell kiln, heated from room temperature to 1400°C over 33 hours, and calcined at 1400°C for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0097] Examples 10-18 are used to illustrate the preparation of the silver catalyst provided by the present invention.

[0098] Example 10

[0099] Weigh 140g of silver nitrate and dissolve it in 150mL of deionized water, weigh 64g of ammonium oxalate and dissolve it in 520mL of deionized water, fully dissolve to obtain a silver nitrate solution and an ammonium oxalate solution, mix the two solutions under vigorous stirring to generate a white silver oxalate precipitate, age for more than 30 minutes, filter, and wash the precipitate with deionized water until there is no nitrate ion. The filter cake contains about 60% by weight of silver and about 15% by weight of water.

[0100] Dissolve 70.0g of ethylenediamine in 75.0g of deionized water, add the silver oxalate filter cake prepared by the above method, continue stirring to dissolve all the silver oxalate, then add 2.58g of cesium nitrate, 6.22g of barium acetate, 0.86g of ammonium perrhenate and deionized water in sequence to make the total mass of the solution reach 400g, and prepare an impregnation solution for standby use.

[0101] Take 20g of the carrier sample prepared in Example 1, put it into a vacuum container, evacuate to above 10mmHg, introduce the above impregnation solution, keep it for 30 minutes, and filter out the excess solution. The impregnated carrier is heated in an air flow at 450℃ for 3 minutes, and cooled to prepare silver catalyst C-1.

[0102] Embodiment 11

[0103] The same as Example 10, except that the carrier sample prepared in Example 2 was used to replace the carrier sample prepared in Example 1. The prepared silver catalyst was C-2.

[0104] Example 12

[0105] The same as Example 10, except that the carrier sample prepared in Example 3 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-3.

[0106] Embodiment 13

[0107] The same as Example 10, except that the carrier sample prepared in Example 4 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-4.

[0108] Embodiment 14

[0109] The same as Example 10, except that the carrier sample prepared in Example 5 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-5.

[0110] Embodiment 15

[0111] The same as Example 10, except that the carrier sample prepared in Example 6 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-6.

[0112] Example 16

[0113] The same as Example 10, except that the carrier sample prepared in Example 7 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-7.

[0114] Embodiment 17

[0115] The same as Example 10, except that the carrier sample prepared in Example 8 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-8.

[0116] Embodiment 18

[0117] The same as Example 10, except that the carrier sample prepared in Example 9 is used to replace the carrier sample prepared in Example 1. The prepared silver catalyst is C-9.

[0118] Comparative Example 1

[0119] This comparative example is used to illustrate the preparation of a reference alumina carrier.

[0120] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of petroleum coke with a median particle size of 18μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0121] Comparative Example 2

[0122] This comparative example is used to illustrate the preparation of a reference alumina carrier.

[0123] 3000g of 25-300μm α-A12O3 trihydrate, 2400g of pseudo-monohydrate A12O3 less than 100μm, 300g of spherical polymethyl methacrylate (PMMA) particles with uniform particle size and diameter of 18μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The kneaded carrier was placed in a bell kiln, heated from room temperature to 1400°C over 33 hours, and calcined at 1400°C for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0124] Comparative Example 3

[0125] This comparative example is used to illustrate the preparation of a reference alumina carrier.

[0126] 3000g of 25-300μm trihydrate α-A12O3, 2400g of pseudo monohydrate A12O3 less than 100μm, 300g of spherical polystyrene (PS) particles with an equivalent diameter of 10μm, 120g of aluminum fluoride and 40g of barium nitrate are put into a mixer and mixed evenly, transferred to a kneader, 140g of vaseline and 2000ml of dilute nitric acid (nitric acid: water = 1:5, weight ratio) are added, and kneaded into a paste that can be extruded. Extrusion molding is a seven-hole columnar object with an outer diameter of 8.0mm, a length of 6.0mm, and an inner diameter of 1.0mm, and drying at 80-120℃ for more than 2 hours to reduce the free water content to less than 10%. The carrier after kneading is placed in a bell kiln, raised from room temperature to 1400℃ over 33 hours, and calcined at 1400℃ for 5 hours to obtain a white α-A12O3 carrier. The measured carrier physical property data are shown in Table 2 below.

[0127] Comparative Example 4

[0128] This comparative example is used to illustrate the preparation of a reference silver catalyst.

[0129] The same as Example 10, except that the carrier sample prepared in Comparative Example 1 was used to replace the carrier sample prepared in Example 1. The prepared silver catalyst was DC-1.

[0130] Comparative Example 5

[0131] This comparative example is used to illustrate the preparation of a reference silver catalyst.

[0132] The same as Example 10, except that the carrier sample prepared in Comparative Example 2 was used to replace the carrier sample prepared in Example 1. The prepared silver catalyst was DC-2.

[0133] Comparative Example 6

[0134] This comparative example is used to illustrate the preparation of a reference silver catalyst.

[0135] The same as Example 10, except that the carrier sample prepared in Comparative Example 3 was used to replace the carrier sample prepared in Example 1. The prepared silver catalyst was DC-3.

[0136] Table 2 Physical properties of carrier

[0137]

[0138] The activity and selectivity of the catalyst samples were measured under the aforementioned process conditions using a microreactor evaluation device. The microreactor evaluation results are listed in Table 3.

[0139] Table 3 Catalyst performance

[0140]

[0141] From the data in Table 2 and Table 3, it can be seen that the carrier provided by the method of the present invention has reduced tortuosity and improved permeability, indicating that the connectivity between the pores of the carrier is improved. The catalyst prepared by the carrier of the present invention has a significantly reduced reaction temperature (i.e., improved reaction activity) and significantly improved selectivity, and has broad application prospects.

[0142] The embodiments of the present invention have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those skilled in the art without departing from the scope and spirit of the described embodiments.

[0143] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

Claims

1. A method for preparing an α-alumina carrier, characterized in that: The steps include: S1. Prepare a solid mixture having the following components: α-A12O3 trihydrate, pseudo-monohydrate A12O3, a pore-forming agent, a burnable lubricating material, a fluoride mineralizer, and an alkaline earth metal compound; wherein the pore-forming agent is a non-spherical organic polymer particle; S2. The solid mixture in step S1, the binder and optionally water are mixed, kneaded and extruded to obtain a molded body; S3. Drying and calcining the molded body in step S2 to obtain the α-alumina carrier.

2. The method for preparing an α-alumina carrier according to claim 1, wherein: The non-spherical organic polymer particles are at least one of rod-shaped particles, peanut-shaped particles, dumbbell-shaped particles, snowman-shaped particles, mushroom-cap-shaped particles, multi-headed particles, disc-shaped particles, particles with concave and convex edges, and particles with protruding rods; The equivalent diameter of the non-spherical organic polymer particles is 0.5 to 50 μm, preferably 2 to 30 μm.

3. The method for preparing an α-alumina carrier according to claim 1, wherein: The organic polymer forming the non-spherical organic polymer particles is at least one selected from the group consisting of polystyrene, polymethyl methacrylate, polyvinyl alcohol, butyl acrylate-methyl methacrylate copolymer, and styrene-methyl methacrylate copolymer.

4. The method for preparing an α-alumina carrier according to claim 1, wherein: The non-spherical organic polymer particles are added in an amount of 0.1 to 20 wt %, preferably 1.0 to 15 wt %, based on the total weight of the solid mixture.

5. The method for preparing an α-alumina carrier according to any one of claims 1 to 4, wherein: The particle size of the trihydrate α-A12O3 is 25-300 μm; the amount of the trihydrate α-A12O3 added is 10-85wt% of the total weight of the solid mixture, preferably 20-82wt%; The particle size of the pseudo-monohydrate A12O3 is less than 100 μm; the added amount of the pseudo-monohydrate A12O3 is 10 to 55 wt%, preferably 15 to 45 wt%, of the total weight of the solid mixture.

6. The method for preparing an α-alumina carrier according to any one of claims 1 to 4, wherein: The burnable lubricating material is vaseline and / or white oil; the amount of the burnable lubricating material added is 0.01 to 8.0 wt % of the total weight of the solid mixture, preferably 0.1 to 5.0 wt %; The fluoride mineralizer is at least one of hydrogen fluoride, aluminum fluoride, ammonium fluoride, magnesium fluoride, and cryolite; the amount of the fluoride mineralizer added is 0.05-8.0wt% of the total weight of the solid mixture, preferably 0.5-5.0wt%; The alkaline earth metal compound is at least one of oxides, nitrates, acetates, oxalates and sulfates of strontium and / or barium; the amount of the alkaline earth metal compound added is 0.01-5.0wt%, preferably 0.05-2.0wt% of the total weight of the solid mixture.

7. The method for preparing an α-alumina carrier according to any one of claims 1 to 4, wherein: The binder is an acid, and the acid is provided in the form of an acid aqueous solution, preferably a nitric acid aqueous solution, wherein the weight ratio of nitric acid to water in the nitric acid aqueous solution is 1:(1.25-10); the amount of the binder is 25-60wt% of the total amount of the solid mixture; Preferably, the binder and pseudo-monohydrate Al2O3 are provided in whole or in part in the form of aluminum sol.

8. An α-alumina carrier prepared by the preparation method according to any one of claims 1 to 7.

9. The α-alumina carrier according to claim 8, wherein The α-alumina carrier has the following characteristics: α-A12O3 content is more than 90%; crushing strength is 30 to 280N / grain, preferably 80 to 180N / grain; specific surface area is 0.3 to 2.5m 2 / g, preferably 1.0 to 2.2 m 2 / g; water absorption rate is 30-75%, preferably 50-70%; pore volume is 0.30-0.90ml / g, preferably 0.45-0.70ml / g; tortuosity is 4-10, preferably 4-7; permeability is 30-200mdarcy, preferably 50-200mdarcy.

10. A silver catalyst for ethylene epoxidation, characterized in that The silver catalyst comprises the following components: a) the α-alumina carrier according to claim 8 or 9; b) an active component silver deposited on component a); c) alkali metals and / or alkaline earth metals, or compounds based on alkali metals and / or alkaline earth metals; d) rhenium metal and / or rhenium-based compounds; as well as e) Optionally, a rhenium co-promoter selected from at least one metal selected from chromium, molybdenum, tungsten and manganese, and / or selected from compounds based on at least one metal selected from chromium, molybdenum, tungsten and manganese.

11. A method for ethylene oxidation, characterized in that: The method comprises: subjecting ethylene to epoxidation reaction under the action of the α-alumina carrier described in claim 8 or 9 and / or the silver catalyst described in claim 10 to obtain ethylene oxide.

Citation Information

Patent Citations

  • Catalyst carrier for producing ethylene oxide as well as preparation method and application of catalyst carrier

    CN107398303A

  • Alpha-alumina carrier and preparation method thereof, silver catalyst for ethylene epoxidation and ethylene oxidation method

    CN115364836A

  • Process for producing porous alpha-alumina catalyst supports

    CN115996791A

  • Catalyst for manufacturing epoxide and method for manufacturing epoxide

    JP2009022835A

  • Shaped porous bodies of alpha-alumina and methods for the preparation thereof

    US20100056816A1